Pemanfaatan Limbah Organik sebagai Pupuk Kompos dan Pupuk Kandang Untuk Pertanian Berkelanjutan - Putra, Atha Esa; Husada, Alfan Setya Putra; Saputra, Wisnu Prayogi; Putri, Tefa Febiola; Ardhiawangsa, Fathiyya B’tari Pradipa; Erbyandhana, Muhammad Afif Razak; Aini, Rifa Ayu Nur; Pramono, Khansa Rizky Febrianti; Fikri, Imam Ikhsanul; Meidista, Salsabilla; Gunawan, Yordan (Universitas Muhammadiyah Yogyakarta, 2025)
The increasing problem of organic waste has become a serious challenge for the environment and agriculture in various parts of the world. These improper disposal practices cause significant environmental pollution, including soil and water pollution, as well as waste accumulation that disrupts public health. On the other hand, the demand for organic fertilizers to support sustainable agriculture is increasing. Sustainable agriculture emphasizes environmentally friendly practices, including the use of organic fertilizers to maintain soil fertility and reduce dependence on chemical fertilizers. The excessive use of chemical fertilizers has been proven to damage soil structure, reduce biodiversity, and pollute water sources. The goal of this program is to enhance public understanding of the importance of agricultural waste management and to provide basic skills in making compost and manure fertilizers. This program also aims to create a more self-sufficient agricultural system by utilizing locally available resources. In addition, the existence of this activity is expected to encourage increased public awareness in maintaining the balance of the agricultural ecosystem by utilizing waste that has not been maximally utilized so far. The methods used in this approach include seminars and demonstrations. Demonstrations were conducted to provide the community with skills in making compost and manure from organic waste available in their surroundings. Through demonstrations, the community can learn directly about the composting process, material mixing techniques, and how to properly manage manure. The results of this activity show an increase in the community's knowledge and skills in processing organic waste into fertilizer. Additionally, there is a heightened awareness among the community about the importance of sustainable waste management and environmentally friendly farming practices. The community is beginning to change their perspective on the use of organic waste as an alternative fertilizer that is more environmentally friendly and economical. This is evidenced by the willingness of several farmers to try applying this technique in their agricultural land, as well as the initiative of the farmer group leader in forming small farmer groups to independently produce compost fertilizer. This activity is expected to make a tangible contribution in reducing the volume of organic waste sent to landfills, improving soil fertility, reducing the use of chemical fertilizers, and supporting the creation of a more environmentally friendly and sustainable agricultural system.